Oregon's Hard-Stop Policy Limiting Elective Early-Term Deliveries: Association With Obstetric Procedure Use and Health Outcomes. Issue 6 (December 2016) - Snowden, Jonathan M.; Muoto, Ifeoma; Darney, Blair G.; Quigley, Brian; Tomlinson, Mark W.; Neilson, Duncan; Friedman, Steven A.; Rogovoy, Joanne; Caughey, Aaron B.
Abstract : OBJECTIVE: To evaluate the association of Oregon's hard-stop policy limiting early elective deliveries (before 39 weeks of gestation) and the rate of elective early-term inductions and cesarean deliveries and associated maternal–neonatal outcomes. METHODS: This was a population-based retrospective cohort study of Oregon births between 2008 and 2013 using vital statistics data and multivariable logistic regression models. Our exposure was the Oregon hard-stop policy, defined as the time periods prepolicy (2008–2010) and postpolicy (2012–2013). We included all term or postterm, cephalic, nonanomalous, singleton deliveries (N=181, 034 births). Our primary outcomes were induction of labor and cesarean delivery at 37 or 38 weeks of gestation without a documented indication on the birth certificate (ie, elective early term delivery). Secondary outcomes included neonatal intensive care unit admission, stillbirth, macrosomia, chorioamnionitis, and neonatal death. RESULTS: The rate of elective inductions before 39 weeks of gestation declined from 4.0% in the prepolicy period to 2.5% during the postpolicy period ( P <.001); a similar decline was observed for elective early-term cesarean deliveries (from 3.4% to 2.1%; P <.001). There was no change in neonatal intensive care unit admission, stillbirth, or assisted ventilation prepolicy and postpolicy, but chorioamnionitis did increase (from 1.2% to 2.2%, P <.001; adjusted odds ratio 1.94, 95% confidence interval 1.80–2.09). CONCLUSIONS: Oregon's statewide policy to limit elective early-term delivery was associated with a reduction in elective early-term deliveries, but no improvement in maternal or neonatal outcomes. Abstract : Supplemental Digital Content is Available in the Text.Although Oregon's hard-stop policy was associated with a reduction in elective early-term deliveries, several perinatal outcomes do not differ between the prepolicy and postpolicy periods.